2015
DOI: 10.1080/15256480.2015.991985
|View full text |Cite
|
Sign up to set email alerts
|

How Do Diners Make Decisions Among Casual Dining Restaurants? An Exploratory Study of College Students

Abstract: Casual dining is a unique sector in the foodservice industry, and consumer decisions in this market are of great interest to marketers. Adopting the well-established Consumer Styles Inventory, this study explores the decision-making styles of college-age diners-an important and emerging growth segment. With survey data collected from a self-administered survey, it identifies five decisionmaking styles adopted by college students: hedonistic, habitual, price conscious, confused by overchoice, and brand consciou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Many of the research studies done over the past 10 years have not worked to identify or re-categorize restaurant segments in the industry in general, but most research studies have specifically analyzed one type of restaurant segment or another. For example, studies recently have primarily focused on casual or casual-themed dining restaurants due to their relative importance and size in the market (DiPietro and Milman, 2008; DiPietro and Partlow, 2014; Dziadkowiec and Rood, 2015; Madanoglu et al , 2008; Murphy et al , 2009; Murphy and Olsen, 2009; Peng et al , 2015; Weiss et al , 2004). In general, casual dining restaurants that are part of a chain have been perceived by guests as being more like fast food restaurants with faster service and more moderate prices than independent casual restaurants.…”
Section: Topics In Foodservice/restaurant Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the research studies done over the past 10 years have not worked to identify or re-categorize restaurant segments in the industry in general, but most research studies have specifically analyzed one type of restaurant segment or another. For example, studies recently have primarily focused on casual or casual-themed dining restaurants due to their relative importance and size in the market (DiPietro and Milman, 2008; DiPietro and Partlow, 2014; Dziadkowiec and Rood, 2015; Madanoglu et al , 2008; Murphy et al , 2009; Murphy and Olsen, 2009; Peng et al , 2015; Weiss et al , 2004). In general, casual dining restaurants that are part of a chain have been perceived by guests as being more like fast food restaurants with faster service and more moderate prices than independent casual restaurants.…”
Section: Topics In Foodservice/restaurant Researchmentioning
confidence: 99%
“…In general, casual dining restaurants meet the expectations of customers (Dziadkowiec and Rood, 2015) with the food and service being the two most important attributes as gleaned from research with casual dining restaurants. These types of restaurants are thought to create more of an overall experience for customers rather than just providing a meal (DiPietro and Partlow, 2014; Peng et al , 2015).…”
Section: Topics In Foodservice/restaurant Researchmentioning
confidence: 99%
“…Casual dining is a unique sector of the foodservice industry. These restaurants "serve moderately priced food, averaging $10 to $40 for dinner per diner, in an informal and relaxed atmosphere with a full-service wait staff" (Peng et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…While their study did not perform market segmentation analysis, the findings indicated that culture traits influence the DMS of travelers. Recently, Peng et al (2015) examined the DMS of college students. The authors identified the following five DMS among the college students: hedonistic, habitual, price conscious, confused by over choice and brand conscious.…”
Section: Literature Reviewmentioning
confidence: 99%